SCHOOL'S CULTURAL DIVERSITY: WHAT IS THE DIFFERENCE BETWEEN "SCHOOL OF HAPPINESS" AND "SCHOOL -PRISON"? - Bubeliene, Daiva; Merkys, Gediminas (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
Five years ago, a questionnaire for senior pupils "Safe School - A Safe Child" was launched in Lithuania. It is a standard inventory containing 160 primary items that are distributed into 38 sub-scales and ultimately into 8 psychometric scales with unusual goodness of fit. At the moment, 2072 pupils' answers appear on the basis of statistical rationing, and 40 different schools in the country are evaluated. A cluster analysis was carried out with scale estimates that reflect the child's psychological well-being and school well-being. In this way, schools were identified at the base of the rationale, which metaphorically converge into a "school of happiness" or a "school prison" model. Then, with the remaining inventory variables, their subscales, the discriminant analysis was carried out. The school type in the model was defined as a grouping variable. Such approach has made it possible to find out which variables, reflecting school's security and livelihood, define the mentioned types of schools. It turned out that the identified types of schools are characterized by such factors as the openness and accessibility of the director; participation of parents and students in school life; sticking to universally accepted, disputed rules; social and pedagogical involvement, sensitivity; avoiding to hide problems and misbehavior. The research data allow on the hypothesis's rights to formulate specific recommendations of the school life improvement for school leaders and educators.